Pengaruh efektivitas dewan komisaris, komite audit dan kepemilikan institusional terhadap efisiensi investasi - Alpha Alan Darma Saputra; Ratna Wardhani (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2017)
This study aims to determine the effect of the effectiveness of the board of commissioners, audit committee, and institutional ownership on the efficiency of corporate investment. In addition to that, it aims to determine the moderation effect of institutional ownership toward the relationship between the effectiveness of the board of commissioners and audit committee with the efficiency of the company's investment. The effectiveness of the board of commissioners and audit committee is measured based on the independency, activity, size, and competence. By using logistic regression with 282 samples from Indonesia Stock Exchange in 2014, the results of this study provide empirical evidence that the effectiveness of the board of commissioners and institutional ownership has no effect on the efficiency of corporate investment, while the effectiveness of audit committees has a positive influence in the efficiency of corporate investment. Furthermore, institutional ownership can not strengthen the relationship between the effectiveness of the board's effectiveness and the effectiveness of the audit committee with the efficiency of the corporate investment. This study contributes to the literature, in which the previous literature has not linked investment efficiency with specific governance mechanisms that relats to effectiveness of the board of commissioners and audit committees. Furthermore, this study contributes to the examination of moderating role of institutional ownership. This study implies that with regard to investment decisions, the audit committee has a significant role in assisting the board of commissioners in carrying out its monitoring functions.